Tissue scaffold architecture affects implant degradation and bone tissue regeneration: A novel in silico mechanobiological model analysing cell behavior, mechanical stress and degradation kinematics - Adel Alshammari; Fahad Alabdah; Lutong Li; Glen Cooper (PLoS ONE, 2026)
Synthetic bone tissue scaffold function is controlled by both material and architecture. Experimental biomaterial approaches have brought significant advances in scaffold function, but scaffold architecture has not been fully explored. There are many scaffold architecture design options which could be more efficiently evaluated using computational methods. The aim of this study is to introduce a novel mechanobiological computational model to assess the effect of implant degradation, bone formation, and the influence of bone loading. A finite element model of a synthetic bone tissue scaffold within a rat bone defect supported by a fixation plate was coupled with an agent-based cell and degradation model (both bulk and surface degradation). The approach was partially validated using in vivo experimental mass-loss data and tested in a case study examining four poly-L-lactic acid tissue scaffolds with varying architectures. The model was run for 90 days to calculate results on cell behaviour, tissue formation and scaffold degradation. The results showed that scaffold architecture strongly influences degradation and cellular behaviour, with a filament thickness of 0.6 mm yielding 39 mm³ of new bone formation compared to 18 mm³ in a filament thickness of 0.2 mm, representing an approximate 117% increase at day 90. Cell migration was increased in higher porosity scaffold architectures by 31% when changing from 20.9% (T4) to 54.7% (T1) porosity. The mechanobiological computational model is, to the authors’ knowledge, the first time that implant degradation kinetics, mechanical environment, and cellular behavior have been combined in an in silico approach. The results show the importance of scaffold architecture design in the function of bone healing aided by tissue scaffold technology, emphasizing the importance of shape as well as material to improve implant function. Future work should aim to improve degradation modelling to include localised pH, autocatalysis and varying degradation rates due to chemical changes. Additionally, models should also include angiogenesis to account for the importance of revascularization in bone healing.